The Analysis of Leaf Traits of Eight Ottelia Populations and Their Potential Ecosystem Functions in Karst Freshwaters in China - Cao, Yu; Liu, Yang; Ndirangu, Leah; Li, Wei; Xian, Ling; Jiang, Hong Sheng (Frontiers in Plant Science, 2019)
Submerged macrophytes play a structuring role in the shallow freshwater ecosystem by increasing the heterogeneous state in freshwaters. The macrophytes in genus Ottelia were featured for their broad leaves, which might consequently produce specialized functions that differed from other submerged species. To explore the potential ecological role of Ottelia, a field investigation was conducted on leaf traits in eight populations of Ottelia ranging from the southwestern Yunnan–Guizhou plateau to the southern Hainan island in China covering a distance of >1,700 km. The eight populations included all the extant Ottelia species and varieties in China except the well-documented O. alismoides. Carbon-related traits [bicarbonate usage, photosynthetic characteristics, capability of Crassulacean acid metabolism (CAM)], pigment content and parameters of chlorophyll fluorescence, morphology and mass of the leaves were determined. The different populations showed distinct functional traits of mature leaves; O. acuminata var. songmingensis had the thickest and longest leaf with CaCO3 precipitation on the both sides of the leaf, and O. cordata showed putative CAM activity with the highest diel acidity changes 12.5 μequiv g-1 FW. Our results indicated an important role of Ottelia populations in carbon cycling as the dominant species in karst freshwaters in China.